Decoding Allergenicity Modulation in Cold Argon Plasma-Treated Casein: A Multi-Omics Exploration - Cai, Ruiyi; Tan, Chin Ping; Lai, Oi Ming; Dang, Yali; Liu, Aiming; Pan, Daodong; Du, Lihui (American Chemical Society, 2025)
Cold argon plasma (CAP) effectively modifies casein (CN) structures by cleaving peptide chains and altering allergenic epitopes. This study assessed the allergenicity of CAP-treated CN in KU812 cells and BALB/c mouse models, supported by a multiomics approach integrating 16S rDNA sequencing, serum metabolomics, and jejunal transcriptomics. CAP treatment reduced CN allergenicity, evidenced by decreased KU812 cell degranulation, alleviated allergic responses in mice, and a Th1/Th2 balance shift toward Th1 dominance. Furthermore, CAP-treated CN restored the gut microbiota equilibrium, increasing the number of beneficial bacteria. Multiomics analysis highlighted its impact on lipid metabolism pathways, with Zbp1 and Hbb-bt identified as potential regulators of allergic responses. These findings underscore the potential of cold argon plasma as an innovative strategy to reduce food allergenicity through multifaceted physiological mechanisms, offering promising therapeutic applications in food allergy management.